Pengaruh rakan sebaya dan pengajaran guru sejarah terhadap sikap pelajar dalam pembelajaran sejarah di sekolah menengah - Arumugam, Vijayaletchumy (2014)
This study aimed to investigate the influence of peers and History teachers towards the attitudes of students in learning history. This study focused on 354 students from eight secondary schools in rural areas and in the city of Kluang. Respondents answered the questionnaire consists of four sections. . The data were analyzed using SPSS. The obtained reliability coefficient for attitudes towards history was at Cronbach’s Alpha .85 and peer influence showed Cronbach's Alpha .81. The influence of the history teacher was Cronbach's Alpha .85. The results demonstrated a high level of student in history acquire the mean score by 4.28. Meanwhile Multiple regression tests were showing that the correlation between students attitudes towards history lesson with the teacher influence was at 0.54 significantly. The correlation between student’s attitudes towards the subject of the history with the influence of peers was at 0.38 significantly. The results showed that student’s attitudes towards the subject of History was at a high level. In addition, the influence of the teacher on the subjects of History showed relatively high level. Peer influence on History subjects was at moderate level. The study also shows that the role of the teacher is very important in learning the history and not much peer influence towards form four students learning history. Several suggestions were made to guide future research.